Perancangan Media Kampanye Keselamatan Lalu Lintas Sejak Dini Melalui Program Transportasi Sehat Merakyat - Hergy Andriawan; Sophia Purbasari; Citra Kemala Putri (Universitas Informatika dan Bisnis Indonesia, 2019)
Early traffic safety campaigns through populist healthy transportation is a government program mandated in Article 203 of Law 22/2009 concerning traffic and road transportation, aimed at reducing the density of traffic flow, minimizing accident rates in adolescents or since early, and reduce air pollution caused by motorized vehicles through populist healthy transportation, including Bikes to School, Walk to School, Bike to Work, and Walk to Work. The campaign was carried out based on police data which stated that school-age students accounted for the largest number of accidents and traffic congestion in Cimahi City. Objectiveity this campaign is to design a traffic safety campaign media early on through effective and efficient public transportation. The design of this data collection was using the Mix Method research method, which was conducting interviews with the Headquarters of the Cimahi Police Satlasa Task Force and Cimahi SMAN 1 students, also distributing questionnaires to Cimahi 1 High School students. The campaign program has not been maximally implemented, both in media and technical implementation, so that it has not been effective in reducing the level of traffic density and traffic accidents by students in Cimahi City.